2017
DOI: 10.1016/j.brs.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Temporal plasticity in auditory cortex improves neural discrimination of speech sounds

Abstract: Background Many individuals with language learning impairments exhibit temporal processing deficits and degraded neural responses to speech sounds. Auditory training can improve both the neural and behavioral deficits, though significant deficits remain. Recent evidence suggests that vagus nerve stimulation (VNS) paired with rehabilitative therapies enhances both cortical plasticity and recovery of normal function. Objective/Hypothesis We predicted that pairing VNS with rapid tone trains would enhance the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Although previous studies have shown plasticity in A1 following VNS, most performed chronic pairing of VNS with sound presentation over many days, e.g., 300 times/day for 20 days Engineer et al (2015b); Shetake et al (2012); Engineer et al (2017, 2011); Borland et al (2019). Here, we studied short-term effects of VNS on auditory learning and cortical plasticity in A1.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have shown plasticity in A1 following VNS, most performed chronic pairing of VNS with sound presentation over many days, e.g., 300 times/day for 20 days Engineer et al (2015b); Shetake et al (2012); Engineer et al (2017, 2011); Borland et al (2019). Here, we studied short-term effects of VNS on auditory learning and cortical plasticity in A1.…”
Section: Introductionmentioning
confidence: 99%
“…Inability of noiseexposed rats to detect silent gaps in narrow-band noise centered on the assumed tinnitus frequency was taken as a behavioral correlate of tinnitus; the gap impairment was eliminated after rats were continuously treated with VSN paired with tones excluding the frequency of tinnitus. To the best of our knowledge, all existing studies replicating these results are from the same group of authors (Shetake et al, 2012;Engineer et al, 2015Engineer et al, , 2017Buell et al, 2019;Adcock et al, 2020). No replication of this work by an independent research team exists.…”
Section: Discussionmentioning
confidence: 88%
“…VNS paired with tones could induce reorganization of the tonotopic map in the auditory cortex, enhancing cortical responses to the paired tone and altering the fields across the entire auditory pathway, increasing the percentage of each field that responds to the paired tone frequency (Engineer et al, 2011(Engineer et al, , 2015(Engineer et al, , 2017Shetake et al, 2012;Buell et al, 2019;Adcock et al, 2020).…”
Section: Vns: Targeting Plasticitymentioning
confidence: 99%
“…These effects can generalize across stimuli. After pairing tone trains at rapid 15 pulse/s with VNS, A1 responses were also increased for unpaired novel speech sounds ( Engineer et al, 2017 ). It has also been demonstrated that VNS modulates synchrony and excitability in the A1 at least in part through the activation of muscarinic acetylcholine receptors ( Nichols et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of VNS-mediated plasticity in the auditory system have measured plasticity following chronic VNS, e.g., 300 times/d for 20 d ( Engineer et al, 2011 , 2015 , 2017 ; Shetake et al, 2012 ; Borland et al, 2019 ). Here, short-term effects of VNS on auditory learning and cortical plasticity were explored.…”
Section: Introductionmentioning
confidence: 99%